Random colonic biopsies in macroscopically normal colonoscopies: is there any benefit? A two‐centre audit of current practice. Issue 12 (28th August 2020) - Seenarain, Vidya; Idrees, Marwan; Mogridge, Jessie; Sinha, Atul; Thompson, Andrew
Abstract : Routine performance of random colonic biopsies should be questioned. These should be performed in selected patients only with a high degree of suspicion of an organic cause of their chronic non‐bloody watery diarrhoea as they otherwise have low yield and are of significant cost. All random colonic biopsies should be placed in one specimen pot when submitted for histopathology analysis as a cost saving measure. Abstract: Background: Recent guidelines from the British Society of Gastroenterology published in April 2018, recommended performing random colonic biopsies (RCB) in endoscopically normal colonic mucosa when investigating chronic diarrhoea in adults to rule out microscopic colitis; however, cost effectiveness was not accounted for due to poor evidence base. There is now more evidence that RCBs are of low yield and of significant cost. Methods: A two‐centre audit of current practice was conducted at Rockingham General Hospital and Fremantle Hospital in Western Australia, aiming to determine the yield of RCB in macroscopically normal mucosa for microscopic colitis, from 1 January 2009 to 30 June 2018, with comparisons of practice and results between gastroenterologists and general surgeons. Variability in the indications (diarrhoea and non‐diarrhoea indications) for RCBs was determined and the cost of consumables, additional endoscopy time and histopathology analysis were calculated. Results: A total of 872 normal colonoscopies with RCBs were included; 48.7% of colonoscopies with RCB were for diarrhoea. Only 1.5% of RCBs were positive for microscopic colitis; 3.1% of patients with diarrhoea had microscopic colitis. Only one patient received pharmacologial treatment as a result of the test. The calculated cost per positive diagnosis of microscopic colitis was $10 862.42. Conclusion: RCBs from normal colonic mucosa have poor yield and are costly. Local guidelines should be updated, so RCBs are performed only in patients with a high degree of suspicion of an organic cause of chronic diarrhoea.